2017
DOI: 10.1038/srep39701
|View full text |Cite
|
Sign up to set email alerts
|

PDLIM5 links kidney anion exchanger 1 (kAE1) to ILK and is required for membrane targeting of kAE1

Abstract: Anion exchanger 1 (AE1) mediates Cl−/HCO3− exchange in erythrocytes and kidney intercalated cells where it functions to maintain normal bodily acid-base homeostasis. AE1’s C-terminal tail (AE1C) contains multiple potential membrane targeting/retention determinants, including a predicted PDZ binding motif, which are critical for its normal membrane residency. Here we identify PDLIM5 as a direct binding partner for AE1 in human kidney, via PDLIM5’s PDZ domain and the PDZ binding motif in AE1C. Kidney AE1 (kAE1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…The N-terminus is truncated by the first 65 amino acids present in the erythroid form of the protein, while a short C-terminus is conserved in both erythroid and renal isoforms 2 . This cytosolic domain interacts with various proteins including carbonic anhydrase II 3 , adaptor protein 1 A&B 4–6 , glyceraldehyde phosphate dehydrogenase 7 , peroxiredoxin 6 8 , and contains a putative type I PDZ binding domain 9 , which interacts with PDLIM5 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminus is truncated by the first 65 amino acids present in the erythroid form of the protein, while a short C-terminus is conserved in both erythroid and renal isoforms 2 . This cytosolic domain interacts with various proteins including carbonic anhydrase II 3 , adaptor protein 1 A&B 4–6 , glyceraldehyde phosphate dehydrogenase 7 , peroxiredoxin 6 8 , and contains a putative type I PDZ binding domain 9 , which interacts with PDLIM5 10 .…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the cytosolic C‐terminal part of kAE1 induces the UPR phenotype. In mammalian cells, it is known that the cytosolic C‐terminus represents an interaction hotspot that modulates the proper transport of kAE1 to the basolateral membrane (Almomani et al, 2012; Su et al, 2011; Su et al, 2017; Toye et al, 2004). Theoretically, the mere lack of such an interaction partner required for proper folding could induce the observed accumulation and misfolding of kAE1 in yeast.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the PDZ domain of PDLIM5 interacts with α-actinin in cardiomyocytes [30]. PDLIM5 also acts as a direct binding partner for Anion exchanger 1 (AE1) via its PDZ domain for membrane targeting [50]. Determining how and which PDZ protein family members specify nAChRs expression, localization, and activity will be an important part of understanding the nature of nicotinic signaling.…”
Section: Discussionmentioning
confidence: 99%